Implementation and Performance of Accounting Information Systems, Internal Control and Organizational Culture in the Quality of Financial Information: Implementación y desempeño de sistemas de información contable, control interno y cultura organizacional en la calidad de la información financiera - SETYANINGSIH, S.D.; MULYANI, S.; AKBAR, B.; FARIDA, I. (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT This study uses a survey method, and the sample used as the unit of analysis in this study is the Consolidated Work Unit at the Financial Bureau or the Financial Center at Ministries and State Institutions throughout Indonesia. The data analysis method uses the Structural Equation Modeling (SEM) approach assisted by the LISREL program. The results showed that the Implementation of Accounting Information Systems, the Implementation of Internal Control Systems, and Organizational Culture significantly influence the Quality of Financial Statements and Performance. RESUMEN Este estudio utiliza un método de encuesta y la muestra utilizada como unidad de análisis es la Unidad de Trabajo Consolidado en la Oficina Financiera o el Centro Financiero en los Ministerios e Instituciones Estatales de Indonesia. El método de análisis de datos utiliza el enfoque de Modelado de ecuaciones estructurales (SEM) asistido por el programa LISREL. Los resultados mostraron que la Implementación de Sistemas de Información Contable, la Implementación de Sistemas de Control Interno y la Cultura Organizacional influyen significativamente en la Calidad de los Estados Financieros y el Desempeño.